Use of Innovative Technologies in Teaching Electrical Engineering - Yakubjon Usmanov; Ikromova Komila Hamidullo qizi (Zien Journals, 2022)
This article provides information on the science of electrical engineering, its development, the main issues of electrical engineering, the properties of electricity, the use of innovative technologies in teaching electrical engineering, the use of information and communication technologies, competence, professional competence, personal competence, methodological competence, innovative approaches.
Keywords: power engineering; competence; technologies; methodological